The study of sustainability report disclosure aspects and their impact on the companies’ performance - Caesaria, Aisyah Farisa; Basuki, B. (2017)
This research is aimed to invetigate the effect of Sustainability Report Disclosure to the Firm’s market performance.Three material aspects disclosed in the Sustainability report such as economics (EC), environmental (EN), and social aspect (SC) are used as the independent variables in this research and, furthermore, the dependent variable is the market performance which is proxied by using Tobin’s Q.This researchs was conducted using mainstream positivistic quantitative methods to test the three formulated hypotheses.The samples taken were 44 observations from all listed companies in the Indonesia Stock Exchange (IDX) that reveal sustainability reports using GRI-G4 guidelines. This guideline is the latest version issued by the Global Reporting Innitiative (GRI), which can be implemented starting from 2013.The results showed that economicss, environmental, and social aspects have positively significant influence to the companies market performance. The practical implication of this research is the value given by society in term of the company image to those companies which disclosure their activities related to economics, social, and environment activities affects their company performance.